MATHEMATICAL LEARNING EFFECTIVENESS THROUGH COOPERATIVE LEARNING MODEL WITH APPROACH PROBLEM OF PROBLEMS IN CLASS XI-IPA SMA NEGERI 1 MAKASSAR - Sakka, Ambo (Pascasarjana Universitas Negeri Makassar, 2013)
The type of this research is quasy experimental research which is aimed to find outwhether the learning of mathematics through cooperative learning model with effective problem applying approach to be applied to circle material on the students of grade XI IPA in SMA Negeri 1 Makassar. The subject of this research is the students of class XI Science SMA Negeri 1 Makassar in the even semester of the school year 2008/2009. The determination of experimental unit used is Cluster random sampling with One Group Pretest-Posttest Desing research design. The number of students in the selected class (class XI IPA-2) as many as 32 people are used as experimental units in this study. Data on teacher and student activity is obtained by using observation sheet while to know the result of student learning used test result of learning. Student response data were obtained by using student response questionnaire. The data analysis used is descriptive analysis to describe the characteristics of each variable. From the analysis results obtained: (1) students are active in following the learning of mathematics through cooperative learning model with the approach of problem solving, (2) teacher activity in learning mathematics through cooperative learning model with problem solving approach very well, (3) student response to learning mathematics Through cooperative learning model with the approach of problem solving is very positive and (4) student learning outcomes after following the learning of mathematics through cooperative learning model with the approach of filing the problem meet the criteria of classical mastery